Cardiovascular complications of systemic lupus erythematosus: impact of risk factors and therapeutic efficacy—a tertiary centre experience in an Appalachian state. Issue 1 (5th May 2021) - McVeigh, Elise Danielle; Batool, Amna; Stromberg, Arnold; Abdel-Latif, Ahmed; Kazzaz, Nayef Mohammed
Abstract : Objectives: Cardiovascular complications became a notable cause of morbidity and mortality in patients with lupus as therapeutic advancements became more efficient at managing other complications. The Appalachian community in Kentucky has a higher prevalence of traditional cardiovascular risk factors, predisposing them to cardiovascular events. Namely, the mean body mass index of the members of the Kentucky Appalachian community was reported at 33 kg/m 2 and 94.3% of male members of this community use tobacco. We sought to identify risk factors that predispose patients with lupus to cardiovascular morbidities and examine the effect of immunomodulatory drugs. Methods: We identified 20 UKHS patients having both a lupus diagnosis and experienced at least one cardiovascular event. We chose three controls matched for birth-year ±5 years to each case. In a case–control design, we analysed lupus manifestations, cardiovascular risk factors and immunosuppressive therapies. We collected Systemic Lupus Erythematosus Disease Activity Index 2000 disease activity index during the cardiovascular event. Results: We identified 308 patients with lupus from among all University of Kentucky Health System patients. 20 (6.5%) of such patients with lupus were confirmed to cardiovascular complication. Of those 20, 7 (35%) had experienced myocardial infarction, 10 (50%) had experienced stroke and 4 (20%) had peripheral ischaemia. Tobacco use and male gender were the only traditional cardiovascular risk factors higher in the cases group. Hydroxychloroquine and steroids were less utilised in the cases than in the controls (70% vs 100% in hydroxychloroquine, 30% vs 82% in steroids). Venous thrombosis was found to be significantly higher in the cases. On multivariate analysis, venous thrombosis remained significant. Conclusion: Despite tobacco use partially explaining the increased risk of cardiovascular disease among the cases group, the higher prevalence of venous thrombosis in the cases group suggests lupus as a potential additional risk factor of cardiovascular morbidity among patients with lupus in this Appalachian community.